Life-cycle environmental assessment of ultra-high-performance concrete with sustainable materials and fiber substitutions - Leila Farahzadi; Lars Gunnar Furelid Tellnes; Behrouz Shafei; Mahdi Kioumarsi (Cleaner Engineering and Technology)
Ultra-high-performance concrete (UHPC) stands at the forefront of cementitious materials used for construction, owing to its unparalleled strength and durability. However, the high cement content and excessive use of steel fibers in the conventional UHPC pose significant carbon dioxide emission and environmental challenges, necessitating the exploration of sustainable alternatives. This study asseses the potential environmental impact reduction achieved by incorporating sustainable materials in UHPC mixtures. The research focuses on replacing conventional UHPC materials with Portland limestone cement (PLC), recycled glass powder, and polyester fibers as lower-impact alternatives. The UHPC mixtures are chosen in a way that falls under the same compressive strength class and offers similar performance characteristics. A life cycle assessment (LCA) methodology is employed to evaluate the environmental performance of different UHPC mixtures. The LCA follows a cradle-to-gate approach, considering key factors such as global warming potential (GWP), energy use, raw material extraction, transportation, and production processes. The results show that substituting ordinary Portland cement (OPC) with PLC and incorporating recycled glass powder reduced the GWP of UHPC mixtures by up to 17%. Moreover, partially replacing steel fibers with polyester fibers further reduced the GWP by 29%. These findings highlight the potential for significant environmental impact reductions in UHPC production through material optimization, contributing to more sustainable construction practices without compromising mechanical performance.